Cytotoxic and NF-κB Inhibitory Constituents of the Stems of Cratoxylum cochinchinense and Their Semi-synthetic Analogues - Ren, Yulin (2011)
A new caged xanthone (1), a new prenylxanthone (2), seven known xanthones, and a known sterol glucoside were isolated from the stems of Cratoxylum cochinchinense, collected in Vietnam. Compounds 1 and 2 were determined structurally by analysis of their spectroscopic data. In addition, five new (10 and 16–19) and eight known prenylated xanthone derivatives were synthesized from the known compounds, α-mangostin (3) and cochinchinone A (6). Several of these substances were found to be cytotoxic towards HT-29 human colon cancer cells, with the most potent being 3,6-di-O-acetyl-α-mangostin (8, ED(50), 1.0 μM), which was tested further in an in vivo hollow fiber assay, but found to be inactive at the highest dose used (20 mg/kg; ip). Of the substances evaluated in a NF-κB p65 inhibition assay, 1,3,7-trihydroxy-2,4-diisoprenylxanthone (5) exhibited the most potent activity (IC(50), 2.9 μM). In a mitochondrial transmembrane potential (MTP) assay, two new compounds, 1 (IC(50), 3.3 μM) and 10 (IC(50), 1.4 μM), and two known compounds, 3 (α-mangostin, IC(50), 0.2 μM) and 11 (3,6-di-O-methyl-α-mangostin, IC(50), 0.9 μM), were active. A preliminary analogue development study showed that 3,6-di-acetylation and 6-benzoylation both slightly increased the cytotoxicity of α-mangostin (3), whereas methylation reduced such activity. In contrast, neither acetylation, benzoylation, nor methylation enhanced the cytotoxicity of cochinchinone A (6).